Fabrication and optical behaviour of nanocomposites from electrodeposited au nanoparticles in polymer microcavities / Tan Kim Han - Tan , Kim Han (2019)
Metal composites and artificial electromagnetic materials might have unusual electromagnetic properties including negative refractive index, highly effective permittivity and permeability values that could be tuned by controlling meta-atoms arrangement, the smallest resonant unit cells in these materials. In this work, a composite of gold nanoparticles (Au NPs) deposited within the polymeric arrays of fringes was demonstrated. The fabrication procedure was suggested by exploiting distinct electromagnetic properties between the ordered polymer molecules and different sizes of Au NPs. The synthesized Au NPs were electrodeposited in the well-ordered square microcavities of positive photoresist (PR) that were formed under electrophoretic deposition (EPD) at 30 DV for 120 sec. The surface plasmon resonance (SPR) of Au NPs and the flexibility of the photoresist (PR) polymer serving as a dielectric made them be used in preparing metal-dielectric nanocomposites. The cavities were constructed from UV-patterning of the PR that was spin-coated on indium tin oxide (ITO) substrate with the assist of copper grids as a photomask. The optical constants become smaller which the highest gain (real permittivity) with the lowest losses (imaginary permittivity) were obtained due to the well-ordered cavities containing the Au NPs. By depositing the Au NPs with different sizes in a relatively ordered manner within the polymeric material, the optical constants and electromagnetic properties of the thin film could be tuned accordingly to suit in applications such as superlens (subwavelength imaging), flat panel displays, optical sensing, and absorbing media.